IMPLEMENTASI KEBIJAKAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DALAM MEWUJUDKAN BUKTI SAH KEPEMILIKAN TANAH DI KECAMATAN BATUKLIANG UTARA KABUPATEN LOMBOK TENGAH - Jayadi, Hapipi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The acceleration of development today has led to a situation where the need for land is increasing. The large amount of land in Indonesia that does not yet have legal certainty over land has triggered disputes and feuds. Since the start of the Complete Systematic Land Registration Program (PTSL) in 2017, around 30 million plots of land have been registered throughout Indonesia, bringing the total number of registered plots to 82 million plots of land. Considering that currently, especially in Batukliang Utara District, Central Lombok Regency, there are still many people who do not have land certificates, with this PTSL program, it is hoped that they will obtain certainty of rights and legal certainty over land and ensure that no problems or disputes arise over land, therefore the community hopes that the government can implement the rules in accordance with the provisions set by the government. This study uses a qualitative approach with a descriptive method. The approach with a descriptive method is based on philosophical principles and explores phenomena owned by groups or individuals. Data collection is done through observation, interviews, and document review. The results of the study concluded that the PTSL program counseling was held in February 2023, which was the initial step to provide an understanding to the community about the benefits and objectives of land certificates. The Complete Systematic Land Registration Policy (PTSL) in Batukliang Utara District, Central Lombok Regency, in 2024 which had been completed as many as 2,400 spread across Karang Sidemen Village as many as 1,000 plots, Aik Berik Village as many as 750 plots, and Setiling Village as many as 650 plots. Community support for the Complete Systematic Land Registration Program (PTSL) in the form of financing so as to facilitate its implementation. A simple division of potential in implementing the policy of forming an Adjudication Committee guided by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency.